2015
DOI: 10.1167/iovs.15-16742
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Changes of Cone Photoreceptors in Eyes With Occult Macular Dystrophy

Abstract: A sparse array of cone photoreceptors with significantly reduced density of the macula is one of the morphologic features of OMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
(43 reference statements)
0
14
0
1
Order By: Relevance
“…Even though the fundus of OMD patients appears normal, recent studies reported the presence of EZ but the absence of CIZ in the SD-OCT images in most of the cases. [37][38][39][40] This condition might indicate that the CIZ is essential for generating the electrical potentials from the photoreceptors in the macular area. Our results showed that the amplitudes of the b-waves at both 1 and 6 months were not significantly correlated with the length of the EZ and CIZ and outer photoreceptor area as shown in Supplementary Figure S3.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the fundus of OMD patients appears normal, recent studies reported the presence of EZ but the absence of CIZ in the SD-OCT images in most of the cases. [37][38][39][40] This condition might indicate that the CIZ is essential for generating the electrical potentials from the photoreceptors in the macular area. Our results showed that the amplitudes of the b-waves at both 1 and 6 months were not significantly correlated with the length of the EZ and CIZ and outer photoreceptor area as shown in Supplementary Figure S3.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] With the development and refinement of optical coherence tomography (OCT), eyes diagnosed with OCMD by electrophysiology were found to have structural abnormalities in spite of the normal appearance of the macula on ophthalmoscopy. 7,[11][12][13][14] Spectral-domain OCT (SD-OCT) imaging has shown subtle morphologic changes including blurring or disruptions in the ellipsoid zone (EZ) of the photoreceptor layer, the absence of the normal ''bowing effect'' and the loss of cone outer segment tips. [11][12][13][14] In 2010, Akahori et al 1 successfully linked the disorder to chromosome 8 and the RP1L1 gene.…”
mentioning
confidence: 99%
“…7,[11][12][13][14] Spectral-domain OCT (SD-OCT) imaging has shown subtle morphologic changes including blurring or disruptions in the ellipsoid zone (EZ) of the photoreceptor layer, the absence of the normal ''bowing effect'' and the loss of cone outer segment tips. [11][12][13][14] In 2010, Akahori et al 1 successfully linked the disorder to chromosome 8 and the RP1L1 gene. So far, a limited number of dominant mutations and variants of uncertain significance have been identified: most important is p.R45W, 1,3,4,15,16 which is recurrently found in all populations irrespective of ethnic descent, and indicative for a mutation hotspot, but also other missense variants have been discussed.…”
mentioning
confidence: 99%
“…We did not assess the CD within 400 lm of the foveal center due to the limit of resolution of the rtx1 systems. [29][30][31][32] The regional sampling method was previously described. 33 The area within an annulus of 0.4-to 2.4-mm diameter was defined as the total annular zone (TAZ) in a 3 3 3mm area ( Fig.…”
Section: Regional Analysismentioning
confidence: 99%